PERLINDUNGAN HUKUM BAGI PENJUAL TERHADAP PERALIHAN HAK ATAS TANAH AKIBAT JUAL BELI YANG BELUM LUNAS - Muhammad, Fachrul; Wira Franciska,; Dhoni Martien, (Journal of Innovation Research and Knowledge, 2026)
In its execution, the Deed of Sale and Purchase (Akta Jual Beli or AJB) adheres to the prevailing customary law and fulfills the principles of "terang" (transparency) and "tunai" (cash payment). However, in practice, it is often found that the AJB is executed even though the payment has not been fully made, and the transfer of land rights to the buyer has already taken place. This study addresses two main research questions: What is the legal protection afforded to the seller in a land sale and purchase where the payment has not been fully settled and What are the legal consequences of transferring land rights based on a Deed of Sale and Purchase executed prior to full payment The study employs the Legal Consequence Theory by Soeroso and the Legal Protection Theory by Philipus M. Hadjon. The research method used is normative juridical (legal research based on library study or secondary data, including primary, secondary, and tertiary legal materials). The approaches utilized in this study include statutory, conceptual, case-based, and analytical approaches. The technique for collecting legal materials involves identifying and inventorying relevant legal norms, legal literature, and other supporting legal documents. The analysis technique applied is based on grammatical and systematic interpretation of legal norms. The findings of this study conclude that the legal consequence of executing an AJB without full payment, followed by the transfer of rights, is that the deed may be annulled through a court decision. Furthermore, legal protection for the seller is guaranteed by law, which provides the seller with the right to file a lawsuit.